The earliest Ordovician nematophorid graptolites: taxonomy and correlation - Erdtmann, B.-D. (Geological Magazine, 1988)
Abstract The earliest nematophorid (planktic) dendroid graptolites (Family Anisograptidae) are described and revised from several heterofacial facies sections of the Broom Point Formation, Cow Head Group, western Newfoundland (Broom Point North and St Paul's represent medial to upper continental slope, Martin Point and Green Point distal slope environments). Noting potential conodont recycling in the palaeoslope environments of the proximal Cow Head Group sections, graptolites are the only group of fossils that could not have been subject to post-burial transport. The graptolites belong to an informal group of quadriradiate form-species principally representing two originally related but then diverging phyletic groups: pendent Rhabdinopora Eichwald, 1855 and horizontal to sub-horizontal Staurograptus Emmons, 1855; both being stratigraphically within Assemblage Zone I (emended after Cooper, 1979) of earliest Tremadoc or early Ibexian age (top of Cordylodus intermedius to base of C. lindstromi conodont zones). Assemblage I graptolites offer a higher resolution than coeval conodonts and are a better tool for inter-facies correlations both within the Broom Point Formation and with other graptolitic sequences on a global scale. Form-species of quadriradiate Rhabdinopora rustica (such as ?R. praeparabola and R. parabola ) and of Staurograptus dichotomus (e.g. ‘Radiograptus’ or ‘Heterograptus’ flexibilis or ‘Aletograptus’ ) are interpreted as astogenetic morphs, or as phylogenetically descendant variants of these forms. Upon evidence of late astogenetic insertion of dissepiments in Staurograptus and Anisograptus the names ‘Heterograptus’ and ‘Radiograptus’ are placed into junior synonymy, and ‘Aletograptus’ is regarded a junior synonym of Staurograptus because its post-primary dichotomies are merely delayed distally (or omitted) to be observed exclusively in very mature specimens. The Cow Head Group fauna is compared with earliest nematophorids from Oslo, Norway (Naersnes) and Dayangcha, Jilin, China (Xiaoyangqiao), ...